2005
DOI: 10.1158/1078-0432.ccr-04-1650
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral COX-2 Gene Expression Is a Predictive Factor for Colorectal Cancer Response to Fluoropyrimidine-Based Chemotherapy

Abstract: Purpose: Cyclooxygenase-2 (COX-2) is generally elevated in tumors compared with normal tissue and apparently has an important role in tumor development. A number of studies have found high expression of COX-2 to be an unfavorable prognostic factor for overall survival in several cancers. However, the influence of COX-2 expression levels on tumor response to chemotherapy has been relatively little studied. The purpose of this study was to ascertain if COX-2 gene expression is associated with tumor response in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
(19 reference statements)
1
20
0
1
Order By: Relevance
“…[30][31][32] Here, the expression level of COX-2 was significantly higher in tumor biopsies compared with tumoradjacent tissues from 26 paired NPC patients (P < 0.05, n D 26), as shown in Fig. 1A.…”
Section: Clinical Impact Of Cox-2 and Mdscs In Patients With Npcmentioning
confidence: 90%
“…[30][31][32] Here, the expression level of COX-2 was significantly higher in tumor biopsies compared with tumoradjacent tissues from 26 paired NPC patients (P < 0.05, n D 26), as shown in Fig. 1A.…”
Section: Clinical Impact Of Cox-2 and Mdscs In Patients With Npcmentioning
confidence: 90%
“…This is based on the premise that many of the COX-2-regulated genes that contribute to tumour progression may also be determinants of tumour sensitivity to treatment (137). Although the potential chemopreventive properties of selective COX-2 inhibitors are being actively investigated, little is known about the utility of these agents in the treatment of cancer.…”
Section: F Serial Changes In Expression Of Various Candidate Proteinmentioning
confidence: 99%
“…Although the potential chemopreventive properties of selective COX-2 inhibitors are being actively investigated, little is known about the utility of these agents in the treatment of cancer. However, there is emerging data from breast, pancreatic and lung cancer studies showing potential benefit of combining COX-2 inhibitors with chemotherapy (137)(138)(139). In particular, a recent study involving patients with heavily pretreated breast cancer showed that the combination of chemotherapy and a selective COX-2 inhibitor resulted in a statistically significant doubling of time to progression for COX-2-positive tumours compared with COX-2 negative ones.…”
Section: F Serial Changes In Expression Of Various Candidate Proteinmentioning
confidence: 99%
“…DCs present in patients with advanced cancer are a target of tumor-associated suppressive factors, resulting in their suppressed ability to support effector functions in tumor-specific lymphocytes (41,42). Known mediators of DC dysfunction include IL-10, TGF-β, VEGF, IL-6, and COX2 products, particularly PGE 2 (4347). DCs that develop in their presence show impaired maturation and reduced expression of costimulatory molecules needed to support T cell activation, and suppressed production of cytokines needed to support survival and anti-tumor effector functions of tumor-specific T cells (5,4851).…”
Section: Therapeutic Vaccines Against Established Cancer: Special Reqmentioning
confidence: 99%